Economic value of watershed conservation of the North Selangor Peat Swamp Forest, Malaysia - Abdulkarim, Buhari (2017)
Forest resources conservation in recent times has shifted from the conventional command and control practices to more dynamic approach such as payment for ecological services (PES) for sustainable management. Forest ecological services are under estimated in development decisions because existing tools for assessing and valuing ecosystem services often fall short of the needs and expectations of decision makers. Thus, the need for better management options such as PES, to ensure sustainable forest management. PES is a new conservation technique that focuses on incentives payments to land owners or stewards for investing in new land use practice that lead to conservation of specific environmental services. The aim of this study is to estimate the economic value of watershed conservation of the North Selangor Peat Swamp Forest (NSPSF). This forest comprises Sungai Karang and Raja Musa Forest reserves. The forest watersheds provides rich ecological functions like flood control, water supply and purification, biodiversity function, carbon storage, pollution control and sediment retention. In addition, recharge water downstream into Sungai Bernam and Sungai Tengi that drains into the agricultural drain land at Barat Laut Selangor irrigation area. However, the watershed is seriously threatened as a result of human activities, coupled with reduction in rainfall (Drought). Consequently, reduce water inflow which poses threat to sustainable supply of water for irrigation and domestic uses in the area. Despite broad recognition of the value of the goods and services provided by the forest watershed, conservation programs in area suffer inadequate funding, hence the need for alternative sources such as PES. To estimate the economic value of this watershed, Contingent Valuation Methods (CVM) and Choice Experiment (CE) was employed. The survey responses of 380 randomly selected farmers and 397 households in the study area were analysed. The result was estimated from a single bounded dichotomous choice contingent valuation (DC-CVM) model and the expected conservation value of the forest watershed from the farmers’ WTP was RM7,319,494,383.85/per/year. For the choice experiment analysis multinomial logit model and Random parameter Model was used. The expected conservation value of watershed obtained from the households’ WTP was RM13,316,102.38/per/year. The result shows that the estimated total economic value of The North Selangor Peat Swamp Forest (NSPSF) for (2016) was RM7,332,810,486.23 billion per year. An important policy implication drawn from the study is that the respondents were willing to pay for improved irrigation and domestic water supply. Therefore, recommend PES as additional conservation funds at the North Selangor Peat Swamp Forest for sustainable conservation and management.